PRODUCT LIABILITY : Fundamental Questions in a Comparative Perspective. - Koziol, Helmut (De Gruyter, 2017)
Where products develop ever more rapidly, the law may face difficulties in responding accordingly to new security threats which may arise. In the field of product liability, an extraordinary need for legal development has thus been perceived, with legislators and judges feeling compelled to find new solutions and to look across borders for these. In the detailed reports in this book, the World Tort Law Society proves that it is in an ideal position to examine the most significant concepts. The report on North America studies the special regime for product liability from its origin in the case law of the US; the European report is centred around the EU Product Liability Directive with its merits and faults; and the influence of these two systems as well as new answers are shown in the reports on Asia, Russia and four key jurisdictions in the rest of the world. Similar questions are discussed worldwide: How can a strict liability regime for products be justified, and can it be justified in all cases? How does the special regime relate to general rules of tort law? Should services be subject to a similar regime? The Members of the Society seek to provoke thought for solutions to these pervasive problems. In this spirit, the volume's comparative conclusions invite discussion, and the book includes four responses to that call from eminent tort lawyers from different legal backgrounds.